PROBLEMS OF TEACHERS’ INTERACTION WITH PRESCHOOLERS AND THEIR PARENTS IN THE CONDITIONS OF MODERN EDUCATIONAL CHALLENGES COVID-19 - Polevikova, Olga; Shvets, Tatiana (Educological discourse, 2020)
The article analyzes the new realities of preschool education in the context of the Covid-19 pandemic; The problems of interaction of teachers with preschoolers and their parents during distance education are singled out, namely among the technological difficulties we first single out the availability of computer equipment, high-speed Internet, the ability to repair any equipment damage during the epidemic. Pedagogical problems include the shortage of staff with universal training, ie those who have modern pedagogical and information technologies and are psychologically ready to work with preschoolers and their parents in the new educational and cognitive network environment. Administrative problems include compiling lists for group training sessions, parent counseling, communication with families and children whose e-mail address has changed. Priority online platforms and tools for working with parents and preschoolers have been identified. The authors also present the positive aspects of distance education for teachers, namely the possibility of free education on various educational platforms; the results of a survey of educators and future bachelors on the problems of distance education of preschoolers in a pandemic. The results of the survey showed that not all the benefits of distance education were realized in the conditions of the epidemic in relation to preschool institutions. For example, due to the workload of adults (both teachers and parents), the network environment, such features as flexibility (education at a convenient time and place), large audience, efficiency, manufacturability (use of new advances in information technology), social equality and, as a consequence, quality were not typical. The most important problem - distance education has shown the inability to provide education and social support for children from poor families (e.g., nutrition).